Improved technological interventions for autumn sugarcane planting - Tyagi, Vikrant; Sanghera, Gulzar S; Singh, Rupinder Pal (Indian Farming, 2018)
To harness higher productivity and better sugar recovery the technological interventions elucidated above and some general considerations given below be advocated to growers and millers. Avoid excessive irrigation and late application of nitrogen (N) fertilizers, when the crop is near maturity. Last application of fertilizer should be completed by June/July. Prevent the lodging of crop by timely propping and earthing up. Protect the crop from frost by light irrigation application during frost period. Harvest the crop at proper maturity stage. Ratoon crop should be harvested first as it matures earlier than plant crop. Cane should be supplied to mills immediately after harvesting by using stipulated quantity of binding material, preferably paddy straw. The afore mentioned agro-techniques led to precision sugarcane farming and help the growers to get higher productivity and returns per unit area under autumn planting of sugarcane crop.